The societal cost of Huntington's disease: are we underestimating the burden?. (27th July 2016) - Jones, C.; Busse, M.; Quinn, L.; Dawes, H.; Drew, C.; Kelson, M.; Hood, K.; Rosser, A.; Edwards, R. T.
Abstract : Background and purpose: Approximately 9000 people in the UK are affected by Huntington's disease (HD). People with HD require ongoing health and social care support. There is a knowledge gap about costs of health and social care use associated with HD in the UK. This paper estimates the economic cost in the UK. Methods: Data on UK patients for the year 2013 were extracted from the European Huntington's Disease Network REGISTRY study, a full clinical dataset, including the full medical history and medication history for patients with HD. National unit costs for the price year 2013 were applied to health and social care services. Results: Data were available for 131 people. The mean annual cost per person with HD was £21 605. The largest proportion of this cost (65%) was due to informal care (£14 085). Conclusions: Informal care was the largest driver of costs across all stages of HD; thus there is a need to also consider the needs of carers when planning services for people with HD.